Evaluating the Influence of Qualifications, Competencies, Managerial Expertise, and Work Discipline on High School Administrative Staff Performance - Sarlota Singerin (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the influence of academic credentials, competencies, managerial skills, and work discipline on the performance of high school academic personnel in Malang City. This research is a descriptive quantitative study employing a purposive sampling strategy to choose a sample of 100 teacher respondents from high schools in Malang City. Purposive sampling was selected to guarantee that participants fulfilled specified criteria pertinent to the research objectives, facilitating more focused and significant data collection. The study's findings reveal that all four variables significantly influence the performance of academic staff, with t-values (academic qualifications: 2.510, competencies: 2.610, managerial abilities: 2.632, work discipline: 2.632) exceeding the critical t-value of 2.036, and corresponding significance values (Sig 0.05) indicating strong statistical relevance. These findings underscore the necessity of targeted professional development programs focused on enhancing academic qualifications, competencies, managerial abilities, and work discipline to bolster academic staff performance. Future research should consider larger, more diverse samples and explore additional variables that could further illuminate factors influencing staff performance. Limitations of this study include the limited sample size and the use of quantitative methods that may not delve deeply into the perceptions and experiences of academic staff.